Effect of A’yun’s predictor software on the behavior, saliva pH, and PHPM index - Quroti A'yun; Ani Subekti (Faculty of Dentistry, Universitas Gadjah Mada, 2018)
Health Research in 2013 showed that 24.8% of children with health problems and dental caries index reached 1.4. A’yun’s Predictor Software (APS) was a new tool to describe the interaction of various factors that play a role in the caries process. The program was developed to establish a better understanding of the multi-factorial aspects of dental caries in children,as well as a guide to improve behavior to reduce the risk of new caries. This study in children aged 10-12 years in SDN Baturan I,SDN Baturan II,SDN Mayangan and SD Muhammmadiyah Trini in Sleman,Yogyakarta.Sampling technique was simple random sampling. This type of research was quasi-experimental control group(pretest and posttest design with control group). The independent variable was oral health education with APS and the dependent variable was the behavior of dental health maintenance oral and mouth, salivary pH and PHPM (Personal Hygiene Performance-Modified)index.Results data were analyzed by t-test. Research shown that there were significant differences between the treatment group and control group on the behavior of the maintenance of oral health of children and PHPM index (p <0.05), while the pH of saliva there was not to be difference (p> 0.05). The conclusions of this study was significant APS application on dental health maintenance behavior oral and mouth, salivary pH, and the index PHPM in school children.